Using Water Stable Isotopes in the Unsaturated Zone to Quantify Recharge in Two Contrasted Infiltration Regimes. Issue 1 (17th May 2018) - Barbecot, Florent; Guillon, Sophie; Pili, Eric; Larocque, Marie; Gibert-Brunet, Elisabeth; Hélie, Jean-François; Noret, Aurélie; Plain, Caroline; Schneider, Vincent; Mattei, Alexandra; Meyzonnat, Guillaume
Abstract : Core Ideas: Soil water stable isotope profiles can be used to quantify groundwater recharge. Climate conditions are recorded in water stable isotope profiles of the unsaturated zone. Soil water isotope profiles provide insight into the seasonality of recharge events. A reliable estimate of recharge is needed for the sustainable management of groundwater resources. Water stable isotope (δ 18 O and δ 2 H) profiles in the unsaturated zone are frequently used to quantify groundwater recharge based on the seasonality of water isotopic compositions in precipitation. A very simple approach consists of integrating the soil water content between peak values of soil water isotopic composition, typically corresponding to precipitation signatures from warm and cold seasons. When precipitation isotopic compositions are available, a conceptual surface water isotopes budget and lumped parameter dispersion model can be computed. These models were applied on two field sites with similar permeable soils with grass cover but contrasting recharge regimes and seasonality, one in the Paris Basin (France) with continuous recharge from autumn to spring and the other in the St. Lawrence Lowlands (Quebec, Canada) with episodic recharge in fall and after snowmelt. For the two sites, the peak‐to‐peak method and isotope surface budget led to comparable recharge intensities. At least at the Paris Basin site, evaporation was shown to slightly modify the average unsaturated zone and hence groundwater isotope composition. The proposed parameterization of isotope fractionation due to evaporation allows qualitative estimation of the fraction of evaporation, at least during the recharge seasons. In spite of its simplifications and limitations, the proposed parsimonious model can give estimates of recharge in a variety of sites even if they are not well characterized, as it benefits from the large availability of monthly isotopic compositions in precipitation.